Respuesta :

Answer:

h'(x)= [tex]e^{x^{9}+In(x) } (9x^{8} +\frac{1}{x} )[/tex]

Step-by-step explanation:

h(x)=[tex]e^{x^{9} +In(x)}[/tex]

first, we will use the chain rule

step1: we divide the function into two parts So,

f(x)=[tex]e^{x^{9} +In(x)}[/tex]   and  g(x)=[tex]x^{9} +In(x)[/tex]

step2: rewrite [tex]x^{9} +In(x)[/tex] as u.

f(x)=[tex]e^{u}[/tex]    and   g(x)=u

step3: differentiate f(x) first.

f'(x)=[tex]e^{u}[/tex]   (the formula is y=[tex]e^{x}[/tex] and y'=[tex]e^{x}[/tex] - the same)

step4: write the value of u for each function but now sub it in the differentiable form of f(x).

f'(x)=[tex]e^{x^{9}+In(x) }[/tex]  and g(x)=[tex]x^{9}+In(x)[/tex]

step5: differentiate the function g(x).

g'(x)=[tex]9x^{8} +\frac{1}{x}[/tex]

(for [tex]x^{9}[/tex] the formula is y=[tex]x^{n}[/tex] and y'=[tex]nx^{n-1}[/tex] ) (for In(x) the formula is y=In(x)  and y'=[tex]\frac{1}{x}[/tex] )

step6: use the chain rule to finish out So,

h'(x)=f'(x) × g'(x)

=[tex]e^{x^{9}+In(x) }[/tex] × [tex]9x^{8}+\frac{1}{x}[/tex]

step7: simplify.

h'(x)= [tex]e^{x^{9} +In(x)}(9x^{8}+\frac{1}{x})[/tex]

ACCESS MORE